High-performance liquid chromatographic determination of amfepramone hydrochloride, mazindol, and diazepam in tablets - Almeida, A. E.; Ribeiro, M. L. (Marcel Dekker Inc, 1999)
Simple and rapid procedures were developed for the quantification of amfepramone hydrochloride and diazepam and mazindol and diazepam in tablets using high performance liquid chromatography (HPLC) with UV detection. These techniques provided conditions for the separation of each active ingredient from the complex matrices of the dosage forms by dilution or extraction in methanol. Isocratic reversed phase chromatography was performed using acetonitrile, methanol, and aqueous 0,1% ammonium carbonate (70:10:20, v/v/v) as a mobile phase, Radial-Pak C-18 column (100 x 8 mm id, 4 mu m), a column temperature of 25+/-1 degrees C and detection at 255 nm. The calibration curves were linear over a wide concentration range (100-1000 mu g.mL(-1) to amfepramone hydrochloride and mazindol and 10-100 mu g.mL(-1) to diazepam) with good correlation factors of 0.9978, 0.9956 and 0.9997 for amfepramone hydrochloride, mazindol, and diazepam, respectively.Mean recoveries obtained from the two kinds of samples ranged from 83.2 to 102.5%, with coefficients of variation ranging from 1.0 to 6.1.These results demonstrated the efficiency of the proposed methods, as well as advantages such as simplicity and short duration of analysis.